1993
DOI: 10.1038/bjc.1993.101
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity on chromosome 6 in human ovarian carcinoma

Abstract: Summary Investigation of genetic changes in tumours by loss of heterozygosity (LOH) is a powerful technique for identifying chromosomal regions that may contain tumour suppressor genes. LOH has been described on chromosome 6 in ovarian carcinoma using restriction fragment length polymorphism analysis with a small number of probes. We studied 29 ovarian carcinomas with 19 probes mapping to chromosome 6. Sixteen of the 29 tumours showed LOH on 6q (55%). Of these 16, 63% showed loss of all informative markers on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…LOH in 6p22-23-detected in more than 30% of penile carcinoma in this study-has also been shown in cervix carcinoma, 20,24 nonsmall cell lung cancer 25 or ovarian cancer, 26 although no correlations to advanced stages or survival could be established. LOH in microsatellite loci D6S260 and D6S1267 is in this study frequently associated with occurrence of metastases and poor prognosis.…”
Section: Discussionsupporting
confidence: 41%
“…LOH in 6p22-23-detected in more than 30% of penile carcinoma in this study-has also been shown in cervix carcinoma, 20,24 nonsmall cell lung cancer 25 or ovarian cancer, 26 although no correlations to advanced stages or survival could be established. LOH in microsatellite loci D6S260 and D6S1267 is in this study frequently associated with occurrence of metastases and poor prognosis.…”
Section: Discussionsupporting
confidence: 41%
“…This is, on the other hand, in keeping with the telomeric position of the region bounded by them. At variance with the fairly well characterized ovarian carcinomas (Zheng et al, 1991;Iwabuchi et al, 1995;Orphanos et al, 1995;Cooke et al, 1996;Sato et al, 1991, Saito et al, 1992Foulkes et al, 1993;Wan et al, 1994;Tibiletti et al, 1996) very few reports have investigated the involvement of chromosome 6 and, in particular of the long arm, in benign surface epithelial ovarian tumors (BOT) (Orphanos et al, 1995) We therefore decided to exploit the information derived from the cloning of the D6S149-D6S193 region to investigate by FISH analysis its integrity in a panel of benign ovarian tumors (BOTs). Besides the above considerations the rationale for this was the recent localization to 6q27, in a region de®ned by markers D6S133 and D6S281, of a locus for SV40-mediated immortalization of human cells (Sandhu et al, 1994;Banga et al, 1997).…”
mentioning
confidence: 97%
“…Keywords: chromosome 6q27; physical map; YAC clones; deletion; benign ovarian tumors The 6q27 region, found to be deleted in ovarian carcinomas and corresponding to loci D6S149 and D6S93 (Saito et al, 1992;Foulkes et al, 1993;Cooke et al, 1996), was cloned by screening CEPH and ICI YAC libraries. With markers D6S149, D6S193 and D6S297 (which is located in between the previous two) used as hybridization probes or for PCR assays, several YAC clones were isolated and characterized (Figure 1 bottom).…”
mentioning
confidence: 99%
“…In an attempt to refine the location of the candidate region we have analysed for LOH using seven polymorphic microsatellite markers on chromosome Sq (Shepherd, 1989). DNA was isolated from tumours and blood as described by Foulkes et al (1993a).…”
mentioning
confidence: 99%